Medicinal Plants Containing Coumarin or Essential Oils from the Brazilian Biome May be New Option for Treating Leishmaniasis? - Silveira, Elizama Shirley; Rodrigues, Naya Lúcia De Castro; Machado, Nuno Miguel de Jesus; Fonseca, Francisco Rafael Marciano; Teixeira, Maria Jania; Leal, Luzia Kalyne Almeida Moreira (Pharmacognosy Reviews)
Leishmaniasis is a neglected tropical disease that is among the 13 most common chronic infections in the world. Current chemotherapy for the treatment of leishmaniasis presents several limitations. Medicinal plants containing coumarins or essential oils have been recognized as products with antiprotozoal and anti-inflammatory activities. Our objective was to collect and analyze the data from the literature on the anti-leishmanial effects of Brazilian medicinal plants, focusing on species that contain coumarins and/or essential oils. A systematic review of the literature on the anti-leishmanial activity of the 94 species of plants listed in the National List of Medicinal Plants Relevant to the Brazilian National Health System and/or “Farmácias Vivas” Program was performed. We searched for original results published by international peer-reviewed journals using three databases (PubMed, ScienceDirect and Scielo), theses and books. We identified 23 plant species belonging to 11 botanical families with anti-leishmanial activity. The medicinal plants (essential oil, crude extract and/or purified fractions) higher leishmanicidal effect in vitro were Bidens pilosa, Eugenia uniflora and Ageratum conyzoides (IC50 ≤ 3.4 μg/ml). Chenopodium ambrosiodes (essential oil) stands out for its antileishmanial activity in vitro and in vivo. Few studies evaluate leishmanicidal activity in vivo models and chemical characterization of natural products is often not carried out or insufficient. The mechanisms of anti-leishmanial action have been related mainly to immunomodulatory activity. This study points to the urgent need to increase research on species that have shown promising leishmanicidal effect. We intend this review to be useful for future researches aiming to develop a new generation of drugs for the treatment of leishmaniasis with low toxicity.
Keywords: Aromatic plants; Coumarin; Leishmaniasis; Phytomedicine; Terpene